(Yearly worked solutions) Pure biology Gce O level 2000-2011 - Khan, ishaq .M (Redspot; Pakistan, 2011)
Biology 5090 (Yearly Worked Solutions) 2000-2011 offers detailed solutions to past exam papers, providing students with a valuable resource to understand and practice key biological concepts for Cambridge IGCSE Biology.